2017
DOI: 10.1111/cge.13009
|View full text |Cite
|
Sign up to set email alerts
|

Copy number variants analysis in a cohort of isolated and syndromic developmental delay/intellectual disability reveals novel genomic disorders, position effects and candidate disease genes

Abstract: We show how phenotypic and genetic analyses of array-CGH data allow unraveling complex cases, identifying rare disease genes, and revealing unexpected position effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
39
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 45 publications
1
39
0
1
Order By: Relevance
“…In this study, the CMA in 63 individuals with DD/ID revealed pathogenic CNVs in 20 (32%) cases. This diagnostic yield is higher than the yields obtained in earlier studies (Miller et al 2010;Wincent et al 2011;Palmer et al 2014;Vianna et al 2016;Di Gregorio et al 2017). However, the reason for this higher detection rate was the inclusion of 12 individuals with abnormal karyotype results prior to the CMA.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…In this study, the CMA in 63 individuals with DD/ID revealed pathogenic CNVs in 20 (32%) cases. This diagnostic yield is higher than the yields obtained in earlier studies (Miller et al 2010;Wincent et al 2011;Palmer et al 2014;Vianna et al 2016;Di Gregorio et al 2017). However, the reason for this higher detection rate was the inclusion of 12 individuals with abnormal karyotype results prior to the CMA.…”
Section: Discussionmentioning
confidence: 57%
“…; Di Gregorio et al . ). However, the reason for this higher detection rate was the inclusion of 12 individuals with abnormal karyotype results prior to the CMA.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, psychotic manifestations and ASD are frequently observed in the clinical practice, and it is particularly worth noting that some patients, diagnosed with ASD in their childhood, show a schizophrenic development in adolescence or adulthood, accompanied by psychotic and neurodegenerative aspects (Keller, Piedimonte, Bianco, Bari, & Cauda, ). These clinical data might be accounted for by finding out common genetic roots at the basis of neurodevelopment disorders, which bring about phenotypic expressions with different timings and modalities, due to epigenetic factors affecting the production of proteins with regulatory function over the brain organization and development (Di Gregorio, et al, ). This hypothesis is supported by the clinical examination of families of patients with ASD, in which phenotypic expressions bear psychiatric disorders different from ASD, OCSD, and SCZD (Biamino, et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Even if TAD-boundary disruption was considered as a well-established model of deleterious mechanism underlying genetic diseases, this mechanism has been shown in only a relatively low number of diseases (Spielmann et al 2018). In addition, large cohort studies identified TAD-boundary disruption as the disease-causing mechanism only in a low proportion of patients, ranging from 0.3% to 11.8% (Di Gregorio et al 2017;Ibn-Salem et al 2014). In light of these data, we wondered whether TAD boundary disruptions could occur without resulting in an observable phenotype.…”
Section: Discussionmentioning
confidence: 99%